1999
DOI: 10.1121/1.424650
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of measured and predicted acoustic fluctuations for a 3250-km propagation experiment in the eastern North Pacific Ocean

Abstract: During the Acoustic Engineering Test ͑AET͒ of the Acoustic Thermometry of Ocean Climate ͑ATOC͒ program, acoustic signals were transmitted from a broadband source with 75-Hz center frequency to a 700-m-long vertical array of 20 hydrophones at a distance of 3252 km; receptions occurred over a period of six days. Each received pulse showed early identifiable timefronts, followed by about 2 s of highly variable energy. For the identifiable timefronts, observations of travel-time variance, average pulse shape, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 27 publications
7
81
0
Order By: Relevance
“…11 because the predictions would have even shorter travel times, making the measured minus predicted travel times more positive. Colosi et al ͑1999͒ find that the observed travel-time variances for the experiment described here are consistent with predictions assuming that the internal-wave field has one-half of the standard GarrettMunk energy level. Using this energy level would reduce the biases in the simulations from Ϫ10 to Ϫ5 ms. Further, the observed pulse spreads are only 0-5 ms ͑Colosi et al, 1999͒.…”
Section: Datasupporting
confidence: 76%
“…11 because the predictions would have even shorter travel times, making the measured minus predicted travel times more positive. Colosi et al ͑1999͒ find that the observed travel-time variances for the experiment described here are consistent with predictions assuming that the internal-wave field has one-half of the standard GarrettMunk energy level. Using this energy level would reduce the biases in the simulations from Ϫ10 to Ϫ5 ms. Further, the observed pulse spreads are only 0-5 ms ͑Colosi et al, 1999͒.…”
Section: Datasupporting
confidence: 76%
“…Second, for both regimes it has been shown that the edges of the shadow zones of the wavefront are significantly extended in depth, and in time [19,20][26]This extension of the shadow zone shows that the effect of scattering in long range low frequency ocean acoustic propagation is to introduce a significant bias into the wavefront intensity pattern; that is to say, the acoustic fluctuations cannot be considered a zero mean effect superimposed upon an otherwise deterministic wavefront pattern. Finally, in spite of the large fluctuations in the wavefront finale the time stability of the phase is surprisingly large and close to that of the wavefront region [22,79,30]. Observed coherence times are between 5 and 15 minutes.…”
Section: Discussionmentioning
confidence: 82%
“…These observations provide significant quantification of space-time scales of ocean sound to Gaussian random noise [22,23]. Second, for both regimes it has been shown that the edges of the shadow zones of the wavefront are significantly extended in depth, and in time [19,20][26]This extension of the shadow zone shows that the effect of scattering in long range low frequency ocean acoustic propagation is to introduce a significant bias into the wavefront intensity pattern; that is to say, the acoustic fluctuations cannot be considered a zero mean effect superimposed upon an otherwise deterministic wavefront pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations